2017
DOI: 10.1039/c7cp01340j
|View full text |Cite
|
Sign up to set email alerts
|

The role of the long-range tail of the potential in O2 + N2 collisional inelastic vibrational energy transfers

Abstract: In the study of non-reactive energy transfer between O and N molecules bearing different vibrationally excited states we have faced the problem of selecting a proper formulation of the interaction. To this end we have compared the values of the related observables computed either on a potential energy surface globally fitted to very large ab initio potential energy values [Varga et al., J. Chem. Phys., 2016, 144, 024310] or on two more traditional ones formulated as a combination of an intra- and inter-molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The DSEC and UCCSD(T)-F12a/AVTZ results show a slight deviation of about 0.2–0.7 kcal mol –1 , while the overall agreement is satisfactory. As can be seen from Figure b,c, the MF2 PES is in good agreement with UCCSD(T)-F12a/AVTZ, consistent with the previous finding that the UCCSD(T)-F12a/AVTZ method is more accurate than the DSEC method for the interaction between rigid N 2 and O 2 . The interactions on the three PESs are slightly different for the long-range interactions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The DSEC and UCCSD(T)-F12a/AVTZ results show a slight deviation of about 0.2–0.7 kcal mol –1 , while the overall agreement is satisfactory. As can be seen from Figure b,c, the MF2 PES is in good agreement with UCCSD(T)-F12a/AVTZ, consistent with the previous finding that the UCCSD(T)-F12a/AVTZ method is more accurate than the DSEC method for the interaction between rigid N 2 and O 2 . The interactions on the three PESs are slightly different for the long-range interactions.…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen from Figure 4b,c, the MF2 PES is in good agreement with UCCSD(T)-F12a/AVTZ, consistent with the previous finding that the UCCSD(T)-F12a/AVTZ method is more accurate than the DSEC method for the interaction between rigid N 2 and O 2 . 15 The interactions on the three PESs are slightly different for the long-range interactions. In Figure 4a, for d within 4.0−5.5 Å, the energies by the PIP-NN method are 0.2−1.0 kcal mol −1 higher than those by the MB-PIP and MB-PIP-NN methods.…”
Section: Overall Fitting Performancementioning
confidence: 99%
See 2 more Smart Citations
“…The vibration-translation (VT) and vibration-vibration (VV) energy transfer was studied by a semi-classical coupled method by Billing on an empirical PES in the range of temperatures between 250 and 1000 K. 23 Recently, Garcia et al 37,38 reported VT and VV RCs using an improved PES for selected vibrational states of oxygen at temperatures up to 7000 K. This PES is based on ab-initio calculations that are interpreted as a combination of van der Waals and electrostatic interaction terms. Unfortunately, the dataset reported in Ref.…”
Section: Resultsmentioning
confidence: 99%